MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DI MTS NEGERI 2 PALAS KABUPATEN LAMPUNG SELATAN - Maysundarwah (UNISAN JURNAL, 2023)
This study describes the management of educators and education staff at MTs Negeri 2 Palas, South Lampung Regency. The purpose of this study was to find out the management implementation of teachers and education staff. This research is included in the descriptive qualitative research with purposive sampling. This study used a qualitative method through a descriptive approach by collecting data through interviews and observations made at the research location. The validity of the data using a data triangulation study. While the data analysis technique uses three stages of analysis namely, data reduction, data presentation and verification. Based on the results of the research conducted, management activities provide training for teachers and collaborate with other teachers. Educators at MTs Negeri 2 Palas are also given duties and responsibilities in managing students, developing, supervising the ongoing educational process and administration related to the teaching and learning process. Management is carried out by the principal as the superior who overshadows the subordinates in carrying out the tasks that are accountable to the teacher as educator.